1996
DOI: 10.4315/0362-028x-59.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Hygienic Characteristics of a Beef Carcass Dressing Process

Abstract: Swab samples were obtained from the surfaces of randomly selected beef carcasses passing through a high-speed dressing process. A single sample was obtained from each selected carcass from one of 10 sites. At each of 3 points in the process, 25 samples were obtained from each carcass site. The aerobic bacteria, coliforms, and Escherichia coli recovered from each sample were enumerated. Values for the means and standard deviations of each set of 25 values were calculated on the assumption that each set of value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 0 publications
2
23
0
1
Order By: Relevance
“…In the present work, we have demonstrated that acid adaptation of E. coli O157:H7 can negatively affect the ability of organic acid spray washing to reduce the numbers of this organism from prerigor BCT. Pathogens contaminating freshly slaughtered beef carcasses typically are recent residents of the bovine gastrointestinal tract, arriving in feces or ingesta from intestinal organs that are accidentally damaged during removal from the carcass or from feces or environmental soil from the hide or hooves (2,24). Organic acid spray washes are used in the early steps of beef carcass processing.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we have demonstrated that acid adaptation of E. coli O157:H7 can negatively affect the ability of organic acid spray washing to reduce the numbers of this organism from prerigor BCT. Pathogens contaminating freshly slaughtered beef carcasses typically are recent residents of the bovine gastrointestinal tract, arriving in feces or ingesta from intestinal organs that are accidentally damaged during removal from the carcass or from feces or environmental soil from the hide or hooves (2,24). Organic acid spray washes are used in the early steps of beef carcass processing.…”
Section: Resultsmentioning
confidence: 99%
“…The latter values became Ϫ3.00 on the log scale while no appreciable difference was made to the nonzero values. This allows all data to be reported while in no way biasing the results (10,11). The statistical package used was Genstat 5 (Rothamsted Experimental Station, Harpenden, United Kingdom).…”
Section: Minmentioning
confidence: 99%
“…A few reports have suggested that hides are a significant source of bacterial carcass contamination (6,10,34,44). Most reports have approached the problem by examining the potential for carcass contamination at critical processing steps by following changes in total aerobic, coliform, or generic E. coli counts or some combination of these (6,(17)(18)(19). These measurements can imply causality but lack the ability to directly link sources with the introduction of specific organisms (contamination events).…”
mentioning
confidence: 99%